Castniinae (Lepidoptera: Castniidae) From Venezuela. V: Castnia fabricius and Telchin Hübner - González, Jorge (Boletín del Centro de Investigaciones Biológicas, 1970)
Abstract Â Information is given for three species of Castniinae (Lepidoptera: Castniidae) found in Venezuela: Castnia fernandezi, Castnia invaria penelope and Telchin licus. Clarifying notes on the genera Telchin and Castnia are provided. Both genera are widely found in Venezuela and contain species that are pests on three major crops.